Combined Genomic and Genetic Data Integration of Major Agronomical Traits in Bread Wheat (Triticum aestivum L.) - Quraishi, Umar M.; Pont, Caroline; Ain, Qurat-ul; Flores, Raphael; Burlot, Laura; Alaux, Michael; Quesneville, Hadi; Salse, Jerome (Frontiers in Plant Science, 2017)
The high resolution integration of bread wheat genetic and genomic resources accumulated during the last decades offers the opportunity to unveil candidate genes driving major agronomical traits to an unpreceded scale. We combined 27 public quantitative genetics studies and four genetic maps to deliver an exhaustive consensus map consisting of 140315 molecular markers hosting 221, 73 and 82 QTLs (Quantitative Trait Loci) for respectively yield, baking quality and grain protein content related traits. Projection of the consensus genetic map and associated QTLs onto the wheat syntenome made of 99386 genes ordered on the 21 chromosomes delivered a complete and non-redundant repertoire of 18, 8, 6 metaQTLs for respectively yield, baking quality and grain protein content, altogether associated to 15772 genes (delivering 28630 SNP-based makers) including 37 major candidates. Overall, this study illustrates a translational genomic approach in transferring information gained from grass relatives to dissect the genomic regions hosting major loci governing key agronomical traits in bread wheat, their flanking markers and associated candidate genes to be now considered as a key resource for breeding programs.